AB0641 "The status of achieving target serum urate levels in the us": analysis from the veterans affairs (va) crystal registry. (23rd January 2014) - Khanna, P.; Reimold, A.; Kerr, G.; Richards, J.; Chang, E.; Schumacher, H.; Singh, J.; Maranian, P.; Khanna, D.
Abstract : Background: CRYSTAL is a longitudinal US registry created in 2008 to standardize and improve care of gout patients at the VA. Gout is the most common inflammatory arthritis managed by VA physicians due to its increasing prevalence and morbidity. Objectives: To explore the proportion of patients who achieved a target serum urate (SUA) target of < 6 mg/dl as recommended by the American College of Rheumatology (ACR) 1 . Methods: Patients from 5 VA sites in the US who met the ACR or New York criteria for gout are currently enrolled. At each visit, gout medications (past and current) and comorbidities are captured. Subjects answer standardized gout-related questions on flares, interval hospitalizations, health assessment questionnaire (HAQ-DI), pain and severity of disease (visual analog scales, 0-10), patient global assessment, and health behaviors. Joint examination is performed to document disease activity; and acute phase markers, SUA, creatinine, and complete blood counts are monitored as part of routine care. Data are presented as mean ± standard deviation (SD) or percentage (%). Results: Of 296 patients, 99% were male with mean (SD) age of 66.7 (11.3) years, 60% were African Americans followed by 37% Caucasians. A 3-year time lag was noted between symptom onset and gout diagnosis, with mean disease duration of 14.9 (13.4) years. Greater than half the cohort had > 3 flares a year (58%). Mean SUA at study entry was 7.5 mg/dL (2.4, n=248) and 68% of patients had levels ≥ 6.0 mg/dL (n=167). Comorbidities included hypertension (n=201 (68%)), hyperlipidemia (n=141 (48%)), diabetes mellitus (n=90 (30%)), and obesity (n=77 (26%)). The mean estimated glomerular filtration rate (eGFR) was 53 ml/min (17.3) and 96% had chronic kidney disease (CKD) defined as eGFR < 90/ml/min (Table ). Urate-lowering therapy (ULT) use at study entry was reported by 212 patients (72%) and allopurinol remained the most prescribed agent. Conclusions: Target serum urate levels were infrequently achieved by patients at first visits despite long duration of disease and reported prescription of urate lowering agents. Improved attainment of target levels in spite of severe gout & renal impairment is being seen on follow up. This supports the need for serial monitoring as can be provided by our Gout Registry. References: Khanna, D., et al., 2012 American College of Rheumatology guidelines for management of gout. Part 1: systematic nonpharmacologic and pharmacologic therapeutic approaches to hyperuricemia. Arthritis Care Res. 2012. 64(10): p. 1431-46. Disclosure of Interest: P. Khanna Grant/research support from: ACR Bridge Funding Award, A. Reimold: None Declared, G. Kerr: None Declared, J. Richards: None Declared, E. Chang: None Declared, H. Schumacher: None Declared, J. Singh: None Declared, P. Maranian: None Declared, D. Khanna: None Declared